Equine Anti-SARS-CoV-2 Serum (ECIG) Binds to Mutated RBDs and N Proteins of Variants of Concern and Inhibits the Binding of RBDs to ACE-2 Receptor - Andrade, Sonia Aparecida; Batalha-Carvalho, João Victor; Curi, Rui; Wen, Fan Hui; Covas, Dimas Tadeu; Chudzinski-Tavassi, Ana Marisa; Moro, Ana Maria (Frontiers in Immunology, 2022)
The COVID-19 pandemic caused by the severe acute syndrome virus 2 (SARS-CoV-2) has been around since November 2019. As of early June 2022, more than 527 million cases were diagnosed, with more than 6.0 million deaths due to this disease. Coronaviruses accumulate mutations and generate greater diversity through recombination when variants with different mutations infect the same host. Consequently, this virus is predisposed to constant and diverse mutations. The SARS-CoV-2 variants of concern/interest (VOCs/VOIs) such as Alpha (B.1.1.7), Beta (B.1.351), Gamma (B.1.1.28/P.1), Delta (B.1.617.2), and Omicron (B.1.1.529) have quickly spread across the world. These VOCs and VOIs have accumulated mutations within the spike protein receptor-binding domain (RBD) which interacts with the angiotensin-2 converting enzyme (ACE-2) receptor, increasing cell entry and infection. The RBD region is the main target for neutralizing antibodies; however, other notable mutations have been reported to enhance COVID-19 infectivity and lethality. Considering the urgent need for alternative therapies against this virus, an anti-SARS-CoV-2 equine immunoglobulin F(ab’)2, called ECIG, was developed by the Butantan Institute using the whole gamma-irradiated SARS-CoV-2 virus. Surface plasmon resonance experiments revealed that ECIG binds to wild-type and mutated RBD, S1 +S2 domains, and nucleocapsid proteins of known VOCs, including Alpha, Gamma, Beta, Delta, Delta Plus, and Omicron. Additionally, it was observed that ECIG attenuates the binding of RBD (wild-type, Beta, and Omicron) to human ACE-2, suggesting that it could prevent viral entry into the host cell. Furthermore, the ability to concomitantly bind to the wild-type and mutated nucleocapsid protein likely enhances its neutralizing activity of SARS-CoV-2. We postulate that ECIG benefits COVID-19 patients by reducing the infectivity of the original virus and existing variants and may be effective against future ones. Impacting the course of the disease, mainly in the more vulnerable, reduces infection time and limits the appearance of new variants by new recombination.